TOKOH PROKLAMATOR NAHDLATUL ULAMA (STUDI HISTORIS BERDIRINYA JAM’IYYAH NAHDLATUL ULAMA) - Ehwanudin Ehwanudin (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2016)
This study of the founders of the organization Nahdlatul Ulama ', which is the largest organization of his followers in Indonesia, is still very interesting to study. Therefore, researchers memunculka four issues: how the background of the birth of Nahdlatul Ulama '?, who Proclaimers character? How objectives to be achieved? In this research study method to figure mengunkap understanding of the persona of an individual in a particular community and in specific areas, revealing views, motivation, life history, and ambitions as individuals through confession, then analyzed using historical analysis, fenomenologig and conten analysis.The purpose of the study is the first, to reveal more about the background of the establishment of Jam'iyya Nahdlatul Ulama (Ulama Awakening). Secondly, To reveal character Jam'iyya Prokalmator establishment Nahdlatul Ulama (Ulama Awakening), third, to reveal the intent and purpose of the establishment of Jam'iyya Nahdlatul Ulama (Ulama Awakening). The conclusion of this study is that the birth Jam'iyah Nahdlatul Ulama 'in essence an attempt to accommodate an existing item. By other terms, the form as jamiyyah diniyyah Nahdlatul Ulama (religious organizations) that currently, merely affirmation formal recognition of informal routines among scholars agree. While birth influenced by several factors namely religious motives, cultivating nationalism and efforts to maintain ahlu understand the Sunnah wal Jamaah. Jam'iyah establishment Nahdlatul Ulama 'initiated by Supreme Master (Hadaratus Sheikh) K.H. M. Hashim Ash'ari, with intent and uphold their end is one of the four schools of Imam, namely: (1) Shafi (2) Maliki, (3) Hanafi (4) Hambali, and do nothing makes serious benefits to religion.